Leading corporate renewal : Selim Bassoul at Middleby Corporation - Shein, James B., 1942-; Meagher, Evan ([London] : SAGE, 2016)
Middleby Corporation was a designer and manufacturer of commercial food processing and food service equipment for fast food as well as high-end restaurants. During the latter half of the 1990s, Middleby became increasingly unfocused as its number of product lines increased dramatically. Margins and sales slipped. At the same time, some of the company's high-profile product development initiatives ended in failure. Although Middleby's top management recognized some of these apparent warning signs, rather than take action, they seemed eager to blame the disappointing results solely on the company's overseas operations. This inaction caused Middleby's financial performance to deteriorate further, resulting in violations of its loan covenants. This case study discusses this topic.
Originally Published in: Shein, J. B., & Meagher, E. (2009). Leading Corporate Renewal: Selim Bassoul at Middleby Corporation. 5-209-253. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Corporate turnarounds -- Case studies; Organizational behavior -- Case studies